The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fncel.2022.880369
|View full text |Cite
|
Sign up to set email alerts
|

Pain Relief in a Trigeminal Neuralgia Model via Optogenetic Inhibition on Trigeminal Ganglion Itself With Flexible Optic Fiber Cannula

Abstract: The trigeminal ganglion (TG) is the primary site of aberration in trigeminal neuralgia (TN), and hence a crucial site where afferent input can be modulated. Here, we postulated that inhibiting TG via optogenetics using flexible optic cannula would diminish brainstem trigeminal nucleus caudalis (TNC) neuronal activity and pain behavior in TN rat model. Infraorbital nerve constriction was employed to induce TN in female Sprague-Dawley rats, while naive and sham rats served as controls. TG-directed microinjection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…We followed the stereotaxic technique to inject the optogenetic virus into TG as mentioned in earlier studies [ 51 , 52 ]. In addition, we employed flexible optic fiber to modulate the TG activity upon stimulation, which ensures high-quality coupling and durability [ 38 ]. Specific targeting and understanding of the molecular perspectives in trigeminal ganglion may help highlight the potential therapeutic intervention in orofacial neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We followed the stereotaxic technique to inject the optogenetic virus into TG as mentioned in earlier studies [ 51 , 52 ]. In addition, we employed flexible optic fiber to modulate the TG activity upon stimulation, which ensures high-quality coupling and durability [ 38 ]. Specific targeting and understanding of the molecular perspectives in trigeminal ganglion may help highlight the potential therapeutic intervention in orofacial neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that thalamic relay nuclei and the trigeminal brainstem, which direct to the somatosensory cortex, are modified by halorhodopsin-mediated inhibition of TG. Additionally, we highlighted that the inhibition has a significant impact on bursting activity and that thehyperpolarization results in a general reduction in thalamic discharge [ 38 ].…”
Section: Trigeminal Ganglion Stimulation Approachesmentioning
confidence: 99%
“…Following ION constriction or sham surgery, anesthetized rats were mounted on a stereotaxic platform for virus injection into our designated brainstem region (TNC). The rat's body temperature was maintained at 36 °C with the aid of a heating pad, and each group received the appropriate viral injection following the previous protocol [ 23 , 24 ]. The coordinates were defined as mediolateral (ML) from the midline, anterior–posterior (AP) from the bregma, and dorsoventral (DV) from the brain's pial surface.…”
Section: Methodsmentioning
confidence: 99%